Beware geeks bearing gifts. (Economist, 1996)
Since 1995, both Microsoft and Netscape have managed to convince millions of Internet users to download beta versions of their Web browsers and document the flaws, with Microsoft even charging users for the privilege of testing Windows 95. Internet software companies contend that the beta system assists in speeding up innovation. However, it also lets them rush out unfinished work and claim that they have developed new features ahead of their competitors.